Climate change, food and nutrition policies in Uganda: Are they gender- and nutrition-sensitive? - Bamanyaki, Patricia A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This brief draws attention to some gaps in the mainstreaming of gender and nutrition in climate change, and food and nutrition-related policy documents, which may affect the effective implementation of nutrition-focused actions and the realization of improved nutrition outcomes.